Study of the Law of Hydraulically Punched Boreholes on Effective Gas Extraction Radius under Different Coal Outputs - Dongdong Xu; Yunqi Tao; Zhengtao Zhou; Chao Hou (Shock and Vibration)
Hydraulic punching technology has recently developed into an effective pressure relief measure and permeability enhancement method for soft and low permeability coalbeds. Different coal outputs directly affect the shape and size of boreholes as well as the effective extraction radius. Taking the Zhongmacun mine as an example, the influence of different coal outputs and different extraction periods on effective extraction radius was analyzed and studied through field tests and numerical simulation. The results show that the increase in coal outputs from hydraulic punching can improve the effective extraction radius of the boreholes. For example, when the gas extraction reaches 90 days, with a coal output of 0.5 t/m, 1.0 t/m, and 1.5 t/m, the effective extraction radius is 3.08 m, 3.46 m, and 3.83 m, respectively. The difference in gas extraction effect of different coal output boreholes increases significantly with the extension of the extraction time, but the speed of growth gradually decreases, which is consistent with the conclusions obtained on-site. This result has important practical significance for optimizing the technical parameters of hydraulic punching, guiding the accurate layout of extraction and drilling, and enhancing the effect of gas control in mines.